The effectiveness of experiential learning modules in increasing problem-solving ability of new employees - Ken Budiarto, Helmy Gania; Fauziah, Puji Yanti; Purwanto, Nurtanio Agus (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
This research aims to know the effectiveness of experiential learning modules in increasing Problem solving ability of new fresh graduate employee in SDIT Assisi and Sari Asih Hospital.  This study employed a quasi-experimental research design that Pre-Post test Control Group Design was utilized in this study's experiment, in which two classes"”treatment and control class"”were used. Data collection techniques included pre and post-test, observation, and documentation.  The results of research on training using EL module show that pre and post-test results obtain a sig. value of 0.056 > 0.05 confidence level, indicating that there is no significant difference in problem-solving ability of fresh graduates using EL module afterward. Meanwhile, the results of pre and post-test in the control and treatment class obtained results with a Sig. value of 0.094 > 0.05 confidence level. Therefore, it can be concluded that there is no significant difference in problem-solving ability of fresh graduate employees between training used EL modules and those that didn't use EL modules.